The Influence of Methods Massed Practice and Distributed Practice Model on The Speed and Accuracy of Service Tennis Courts - Wiwin, Desak; Mintarto, Edy; Nurkholis, Nurkholis (Universitas Negeri Semarang (Unnes), 2017)
The purpose of this study was to analyze about (1) the effect of the method massed practice against the speed and accuracy of service, (2) the effect of the method of distributed practice against the speed and accuracy of service and (3) the influence of methods of massed practice and distributed practice against the speed and accuracy of service. This type of research used in this research is quantitative with quasiexperimental methods. The research design uses a non-randomized control group pretest posttest design, and data analysis using Manova. The process of data collection is done by testing the speed of service (dartfish) and test accuracy (Hewitt) during the pretest and posttest. The results of the study as follows: (1) there is a significant influence on the methods of massed practice to increase the speed and accuracy of service (2) there is a significant influence on the method of distributed practice to increase the speed and accuracy of service (3) There is no significant difference influence among methods massed ptactice practice and distributed to the speed and accuracy of service. Conclusions of this research is a method massed practice and distributed practice equally provide significant results but that gives the influence of better is method distributed practice to speed and accuracy of service.